C atoms versus Si atoms at the bridgehead positions of phenyl-decorated adamantane-type clusters: influence on the nonlinear optical response - Ziese, Ferdinand; Dehnen, Stefanie; Sanna, Simone; Justus Liebig University Giessen (My University, 2026)
In order to explore the effect of the presence of CPh versus SiPh parts on the optical nonlinearities of phenyl-decorated adamantane-type clusters, the second harmonic generation (SHG) spectra of molecular clusters with the general formula [(CPh)x(SiPh)4−xS6] and x = 0,…, 4, are calculated within (hybrid) density functional theory. The stepwise replacement of C atoms with Si at the bridgehead positions leads to the blue-shift of the first SHG peak and to a redistribution of the spectral weights of the different signatures. The electronic transitions related to the SHG peaks are found to occur mainly at the substituents, which are common to all investigated compounds. However, the peak intensity strongly depends on the substitution induced distortion of the cluster core. Thus, although the cluster core is not directly involved in the genesis of the optical nonlinearities, it heavily impacts their intensity. The presented results suggest that reducing the core symmetry provides a pathway to enhance the SHG response of the clusters and yields a theoretical foundation for the design of nonlinear optical materials with tailored properties.
Keywords: ddc:530